2018
DOI: 10.3390/app8091537
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Strength Characteristics of Cemented Tailings Backfill with Alkali-Activated Slag

Abstract: With the use of glauberite mineral (GM) and sodium hydroxide (SH) alkaline catalysts to stimulate slag powder’s internal cementation activity and incorporate the two fine-grained solid wastes, such as quicklime (Q) and desulfurized ash (DA), a new cementitious material suitable for mine tailings was developed to replace traditional ordinary Portland cement (OPC) for reducing cement-related costs. A series of uniaxial compressive strength (UCS) tests were carried out on cemented tailings backfill (CTB) samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…Alkali-activated binders could be designed to have superior properties compared to cement, namely the development of earlier and higher mechanical strengths [22], better resistance to acids and sulphates [23], and lower heat of cement hydration [24]. Numerous studies [17,18,[25][26][27] have been recently shown to better assess the mechanical, workability and microstructural properties of CPB materials by using alkali-activated slag (AAS) as a binder. These studies have shown that, compared to those made up of OPC, CPB samples containing AAS as binder were found to produce remarkably higher early-age strength and stability.…”
Section: Introductionmentioning
confidence: 99%
“…Alkali-activated binders could be designed to have superior properties compared to cement, namely the development of earlier and higher mechanical strengths [22], better resistance to acids and sulphates [23], and lower heat of cement hydration [24]. Numerous studies [17,18,[25][26][27] have been recently shown to better assess the mechanical, workability and microstructural properties of CPB materials by using alkali-activated slag (AAS) as a binder. These studies have shown that, compared to those made up of OPC, CPB samples containing AAS as binder were found to produce remarkably higher early-age strength and stability.…”
Section: Introductionmentioning
confidence: 99%
“…As the mining depth continues to increase and governments vigorously promote green mining methods, the filling mining method has become increasingly more widely used for underground metal deposits in China [4,5]. Meanwhile, many scientific research developments have been achieved in backfill mining technology, backfill materials, and the mechanical properties of backfills [6][7][8][9][10][11]. For example, Mirzababaei et al [12][13][14] studied the behavior of soft clay reinforced with short fibers, and found sand ratio of the backfill body, the changing range of the average infrared radiation temperature (AIRT) of the backfill body became increasingly smaller [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…High-water-content backfill material [34][35][36], as a special backfill material used in coal mines in China, contains more than 90% water, has been quite mature in the testing method of mechanical characteristics, backfilling technology and equipment, and has achieved a good backfilling effect in the application of coal mine engineering. As buildings and infrastructures in the ground surface should be protected during and after coal mining, backfill mining has been widely used in China [37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%